Glaucoma visual field quantification with eye tracker - Yu, Wangyang; Tang, Jingyu; Zhang, Yudong; Hu, Menghan; Wu, Yue (Displays, 2023)
Glaucoma is a group of diseases that manifest as atrophy and depression of the optic papilla, visual field defects, and vision loss, representing one of the three leading causes of blindness worldwide. Traditional visual field examinations – an important diagnostic tool for glaucoma – present various challenges including patients’ inability to maintain fixed vision, delays in detecting vision loss, passive position detection, difficulty in detection, and limitations in reflecting physiological visual field damage. Early diagnosis and intervention are crucial for improving patients’ condition and enhancing their later-life abilities and life quality. Herein, we proposed two vision field detection systems to overcome these limitations. First, we establish a dynamic visual field detection system to reduce the complexity of traditional detection experiments and to enhance their operability. Instead of fixating on a central point, subjects are only required to search for the target in the picture. We analyze the heat map and trajectory map of visual attention for visual interpretation, and the analysis of experimental data reveals that the average finding time of subjects in the experimental task varies. In response to the scenario where visual field defects are not detected by the dynamic visual field detection system, we have developed a static visual field detection system based on the former. The system obtains eye movement data and automatically generates a map of the extent of the physiological blind spot without any action required from the patient. The experiment results provide evidence for the effectiveness of the static visual field detection system in detecting the physiological blind spot. Given the well-established association between glaucoma and an enlarged physiological blind spot, the use of an eye tracker to assess the extent of the subject’s blind spot represents an easy-to-use and reliable method for preliminary glaucoma screening. •We propose two visual field detection systems based on eye-tracking device.•We develop a dynamic visual field detection system, reducing the complexity of traditional examination device.•We develop a static visual field detection system without any action required from the subjects.